Double-stranded RNA virus in the human pathogenic fungus Blastomyces dermatitidis. - Kohno, S (1994)
Double-stranded RNA viruses were detected in a strain of Blastomyces dermatitidis isolated from a patient in Uganda. The viral particles are spherical (mostly 44 to 50 nm in diameter) and consist of about 25% double-stranded RNA (5 kb) and 75% protein (90 kDa). The virus contains transcriptional RNA polymerase activity; it synthesized single-stranded RNA in vitro in a conservative manner. The newly synthesized single-stranded RNA was a full-length strand, and the rate of chain elongation was approximately 170 nucleotides per min. The virus-containing strain shows no morphological difference from virus-free strains in the mycelial phase. Although the association with the presence of the virus is unclear, the virus-infected strain converts to the yeast form at 37 degrees C, but the yeast cells fail to multiply at that temperature.